Efficacy of systemic insecticides against the citrus mealybug, Planococcus citri, and pesticide mixtures against the western flower thrips, Frankliniella occidentalis, in protected environments - Willmott, Amy Lynn (Kansas State University, 2012)
Protected environments, such as greenhouses and interior plantscapes provide optimal conditions for arthropod (insect and/or mite) pests to survive, develop, and reproduce. Two commonly encountered insect pests in protected environments include the citrus mealybug (CMB), Planococcus citri, and the western flower thrips (WFT), Frankliniella occidentalis. It is difficult to mitigate CMB and WFT populations due to the behavioral characteristics of the insects and few pesticides that are registered for use in protected environments. This research involved two distinctly different studies. The objectives of the first study were to determine the efficacy and residual activity of systemic insecticides registered for use against CMB and to quantify CMB feeding locations. The objectives of the second study were to determine the compatibility and efficacy of commonly used binary pesticide mixtures against the WFT under both laboratory and greenhouse conditions. To determine the efficacy of systemic insecticides against CMB, greenhouse experiments were conducted in which coleus, Solenstemon scutellarioides, plants were artificially infested with CMB. Drench applications of each designated treatment were applied to each plant. Results associated with drench applications of the systemic insecticides against CMB indicated minimal CMB mortality (<30%) for both preventative and curative drench applications of azadirachtin and spirotetramat. Thiamethoxam, a neonicotinoid-based insecticide, at the labeled and twice the labeled rate provided the highest CMB mortality; however, not until 21 days after treatment was this observed, and CMB mortality was <80%. In all cases, significantly more CMB were located on the stem of green coleus plants compared to the leaf top and bottom. Pesticide mixture compatibility was determined using jar tests. In addition, phytotoxicity and efficacy of pesticide mixtures against WFT was determined through a series of laboratory and greenhouse experiments for each individual pesticide, and the mixtures to determine synergism, antagonism, or no effect. Results associated with the jar tests indicated that all the mixtures were compatible. Furthermore, the mixtures were not phytotoxic to the horticultural plant species evaluated. Laboratory results indicated that mixtures containing spinosad + bifenazate were antagonistic against WFT. Greenhouse experiments demonstrated significantly reduced efficacy associated with the abamectin + azadirachtin mixtures; however, each binary mixture provided approximately 80% mortality of WFT.
Keywords: Citrus mealybugs; Systemic insecticides; Western flower thrips; Pesticide mixtures; Greenhouses; Interior plantscapes; Entomology (0353)